Laozi, the life worth living - Parreño Piñol, Manuel (Sinología hispánica. China Studies Review, 2021)
The purpose of this paper is to show how, according to Laozi (the author) and based on the Laozi (the book), everyone has the ability to achieve an acceptable degree of goodness. Laozi lays out his understanding of goodness as a mystical ideal, which, for Laozi, this makes sense due to the close link he sees between goodness and Dao. Thus, the scope this paper covers is the population of the world, as it deals with mankind’s potential for goodness. This study has not been designed to investigate the meaning of Laozi’s concept of goodness. Instead, the focus is on the fact that, according to Laozi, we have come into existence because of Dao and have been given of Dao the means to know what decisions are naturally called for or good; According to Laozi’s natural understanding of the world. Consequently, this paper seeks to answer questions such as: How is it that all can lead a life in line with goodness? Why is it that so many do not lead such a life? How does philosophy allow or help us to become our best self? The model was selected from particular chapters of Laozi teaching on the concept of goodness which, in Laozi, is equally represented in the behavior or manner of acting of Dao, Naturalness, the Sage and ‘‘water.’’ Dao as the fountain of all that is good; Naturalness as the law by which when acting spontaneously, innately, we know of Dao’s ways; The Sage as the example of the ideal man; ‘‘water’’ as the metaphor Laozi uses to speak of ‘‘the highest good’’.